2010
DOI: 10.1142/9789814282321_0010
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization between Coupled Oscillators: An Experimental Approach

Abstract: We present an experimental set-up that allows to study both controlled and uncontrolled synchronization between a variety of different oscillators. Two experiments are presented where uncontrolled synchronization between two types of identical oscillators is investigated. First, uncontrolled synchronization between two Duffing oscillators is investigated and second, uncontrolled synchronization between two coupled rotating elements is discussed. In addition to experimental results we provide both analytical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In Section 3, it has been shown that this is also true for the case where the metronomes are replaced by two self-driven discontinuous mass-spring-damper oscillators. Obviously, this result suggests that this may be true for other second order nonlinear oscillators [19,22,23].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In Section 3, it has been shown that this is also true for the case where the metronomes are replaced by two self-driven discontinuous mass-spring-damper oscillators. Obviously, this result suggests that this may be true for other second order nonlinear oscillators [19,22,23].…”
Section: Discussionmentioning
confidence: 72%
“…Clearly, in closed loop, the dynamics of Eq. (1) with controllers (18)- (19) coincide with the dynamics of Eq. (9).…”
Section: Adjustment Of the Experimental Setup To Mimic Huygens' Systemmentioning
confidence: 86%
See 2 more Smart Citations
“…This type of coupling arises in various areas of science arranging from physiology 16,17 and neuroscience [18][19][20][21][22] to electrical systems 23,24 and mechanical engineering. [25][26][27][28] In addition, we allow the coupling to contain time-delays, which can arise due to finite propagation speed of information and/or the time it takes to make decisions, cf. Ref.…”
Section: Introductionmentioning
confidence: 99%